2003
DOI: 10.1073/pnas.242741799
|View full text |Cite
|
Sign up to set email alerts
|

Oncogenic targeting of an activated tyrosine kinase to the Golgi apparatus in a glioblastoma

Abstract: Activating oncogenic mutations of receptor tyrosine kinases (RTKs) have been reported in several types of cancers. In many cases, genomic rearrangements lead to the fusion of unrelated genes to the DNA coding for the kinase domain of RTKs. All RTK-derived fusion proteins reported so far display oligomerization sequences within the 5 fusion partners that are responsible for oncogenic activation. Here, we report a mechanism by which an altered RTK gains oncogenic potential in a glioblastoma cell line. A microdel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
70
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 79 publications
(71 citation statements)
references
References 42 publications
1
70
0
Order By: Relevance
“…This 240 kb deletion has been well characterized previously, and occurs between intron 7 of Fused in Glioma (FIG) and intron 35 of ROS resulting in a FIG-ROS fusion protein with constitutive kinase activity. 25 Molecular cytogenetic and expression analysis. FISH experiments were performed to confirm copy number changes identified by array CGH.…”
Section: Resultsmentioning
confidence: 99%
“…This 240 kb deletion has been well characterized previously, and occurs between intron 7 of Fused in Glioma (FIG) and intron 35 of ROS resulting in a FIG-ROS fusion protein with constitutive kinase activity. 25 Molecular cytogenetic and expression analysis. FISH experiments were performed to confirm copy number changes identified by array CGH.…”
Section: Resultsmentioning
confidence: 99%
“…However, the consequences of ectopic ROS expression on tumorigenesis have never been addressed experimentally. We recently characterized a small interstitial microdeletion on 6q21 in two human glioblastoma cell lines that result in the fusion of a Golgi apparatusassociated protein, called FIG, to the kinase domain of ROS (11,12). We also showed that the result of this event is similar to the intragenic deletion of exons 2 to 7 of the epidermal growth factor receptor (known as vIII) found in a substantial percentage of glioblastoma multiformes, which is the creation of a constitutively activated ligandless version of its cognate full-length receptor.…”
Section: Introductionmentioning
confidence: 99%
“…CFTR (cystic fibrosis transmembrane regulator)-associated ligand (CAL) (Cheng et al, 2002) is cloned, characterized and named after each context of finding by several groups, for example, Golgi-associated PDZ and coiled-coil motif-containing protein (Yao et al, 2001), PDZ protein interacting specifically with TC10 (PIST) and fused in glioblastoma (Charest et al, 2001). CAL is composed of 454 amino acids forming two coiled-coil domains and one PDZ domain by which it dimerizes and interacts with other cellular counterparts.…”
Section: Introductionmentioning
confidence: 99%
“…CAL is also associated with targeting of other plasma membrane proteins such as Wnt receptors, Frizzled 5 and 8 (Yao et al, 2001), an EGF receptor family, CALEB/NGC (Hassel et al, 2003) and a chloride channel protein, ClC-3B (Gentzsch et al, 2003). It is supposed that CAL takes part in their intracellular trafficking, which was evidenced by interaction with a Q-SNARE protein, syntaxin 6 (Charest et al, 2001), and a small GTPase, TC10 regulating the translocation of the insulin-stimulated glucose transporter, GLUT4 to plasma membrane (Chiang et al, 2001;Neudauer et al, 2001). Furthermore, the fact that CAL is involved in autophagy in neuronal cells by binding both GluRd2 and Beclin1 (Yue et al, 2002), and in acrosome formation in mice sperm (Yao et al, 2002), also supports the implication of CAL in the vesicular trafficking pathway between membranous organelles such as the Golgi, plasma membrane, endosome and lysosome.…”
Section: Introductionmentioning
confidence: 99%